An approach to the modelling of stability of waste containers during urban flooding. (19th August 2019) - Martínez‐Gomariz, Eduardo; Russo, Beniamino; Gómez, Manuel; Plumed, Aurea
Abstract: Before the solid waste is dumped in landfills, the collection process for large Spanish cities starts from a regular collection of household waste municipal service which is carried out through street containers. When an urban flood occurs those containers may lose their stability, thereby allowing debris (i.e., solid waste contained) and leachate to escape from the container and contaminate the flood water. Moreover, once a container loses its stability it can further constrict a narrow street and increase flooding, thereby creating a closed basin with no outlet for runoff and exacerbating the effects of flooding. Therefore, the waste containers stability when exposed to flooding is definitely an environmental, safety and health concern to be addressed. In this research stability functions for waste containers exposed to urban floods have been derived. These thresholds have been employed to analyse the containers' potential behaviour during floods in Barcelona. In order to validate the model a historical rainfall has been modelled and low‐return‐period design storms (i.e., 1, 5, and 10 years) have been used to assess the containers vulnerability against floods for frequent rainfall events. Once the number of potentially unstable containers has been estimated, an adaptation measure has been proposed in order to increase the resilience of waste sector against urban floods in Barcelona.